A review of photochemical approaches for the treatment of a wide range of pesticides - 김기현 (JOURNAL OF HAZARDOUS MATERIALS, 2015)
Pesticides are renowned as some of the most pernicious chemicals known to humankind. Nine out of twelve most hazardous and persistent organic chemicals on planet have been identified as pesticides and their derivatives. Because of their strong recalcitrant nature, it often becomes a difficult task to treat them by conventional approaches. It is well perceived that many factors can interfere with the degradation of pesticides under ambient conditions, e.g., media, light intensity, humic content, and other biological components. However, for the effective treatment of pesticides, photochemical methods are viewed as having clear and perceivable advantages. In this article, we provide a review of the fundamental characteristics of photochemical approaches for pesticide treatment and the factors governing their capacity and potential in such a process. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Photochemical methods; Pesticide treatment; Photocatalytic degradation; Photocatalysis